PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW DALAM MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SD NEGERI 48 PAREPARE - Djabba, Rasmi (Fakultas Keguruan dan Ilmu Pendidikan, 2020)
The problem addressed in this study is to apply the jigsaw cooperative learning model to improve the affectifeness and autcomes of learning science fifth grade students of SDN 48 parepare. The objective to be achieved is to thetermine the application of jigsaw cooperative learning model to improve the effectiveness and autcomes of learning science fifth grade students of SDN 48 Parepare.This study used a qualitative approach to this type research is action research is action research. The results of this study show that the effectiveness and increasedstudent learning outcomes in teachimg science as applied jigsaw cooperative learning model.It shows that the jigsaw cooperative learning model to improfe the effectifeness and learning outcomes siswa pada teaching science classes SDN 48 Prepare